Singlish particles and politeness work in face-threatening speech acts - Lai, Yun-Sxin (2023)
Having been thought to be ‘crass’, ‘uneducated’ and ‘unintelligent’, Singlish, also commonly known as Singapore Colloquial English, is perceived to be an impolite language. In particular, Singlish particles, which are purportedly Singlish’s most distinctive feature, have been said to exacerbate threats to addressees’ negative and positive face. However, existing literature has found that in informal speech settings, Singlish may actually be beneficial for politeness, mainly by virtue of its status as a language of solidarity. This article seeks to explore the relationship between Singlish particles and politeness, by investigating the use of particles within two types of inherently face-threatening speech acts–assertions and directives–and how these particles boost politeness by mitigating the face threats present in these speech acts. Our analysis of 72 hours of conversational data suggests that Singlish particles hold much potential to help speakers appeal to their addressees’ positive face needs in informal settings.